2010
DOI: 10.1186/1758-5996-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Absence of diabetic retinopathy in a patient who has had diabetes mellitus for 69 years, and inadequate glycemic control: case presentation: response

Abstract: A response to Jorge Esteves, Carolina Maurente da Rosa, Caroline Kaercher Kramer, Luiz Eduardo Osowski, Stéfano Milano and Luís Henrique Canani: Absence of diabetic retinopathy in a patient who has had diabetes mellitus for 69 years, and inadequate glycemic control: case presentation. Diabetology & Metabolic syndrome 2009, 1:13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This probably indicates effective medical, laser, and surgical intervention practices in place or spontaneous resolution of DR without any intervention. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…This probably indicates effective medical, laser, and surgical intervention practices in place or spontaneous resolution of DR without any intervention. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…low lipid levels, hypogonadism, growth hormone deficiency, reduced IGF-1 levels, high myopia, raised intraocular pressure and moderate carotid stenosis. 34 41 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that patient characteristics such as age, type of diabetes control and HbA1C levels, in the pre-treatment, treatment and post-treatment period could affect the response to medications used for treatment of diabetic retinopathy (DR). [ 23 24 25 26 ] Furthermore, other studies have reported the effect of genetic factors and other patient characteristics on the response to intravitreal ranibizumab therapy in age-related macular degeneration (ARMD). [ 27 28 29 ] Thus, comparing the efficacy of various DME treatment protocols, baseline and systemic individual factors should be taken into account.…”
Section: Introductionmentioning
confidence: 99%